Impact of the educational program “Igiene Insieme”in 1,991 Italian primary schools: student behavior and incidence of SARS-CoV-2 - Bricchi, Lucia; Signorelli, Carlo; Odone, Anna; Cereda, Danilo; Bisceglia, Lucia; Lopalco, Pier Luigi (Acta Biomedica Atenei Parmensis, 2023)
Objective: To evaluate the impact of the health educational program “Igiene Insieme 2021/2022” on Italian primary school children’s knowledge, attitudes and practice of hygiene and sanitation and to compare incidence of SARS-CoV-2 in schools participating the project with regional data of Lombardy and Apulia. Methods: Participating schools were provided with a hygiene kit containing educational material for teachers and sanitizing products for students. We conducted a pre-post evaluation administering a questionnaire before and after the intervention. In addition, we compared SARS-CoV-2 incidence of the participating primary schools (225 in Lombardy and 120 in Apulia) to regional-level data. We tested the differences between groups by using the Chi-squared test. Results: Of 1,991 schools, 472 responded to both questionnaires for a total of 16,988 students. 17.3% of the students learned the importance of handwashing in preventing infections, 22.6% when to wash hands, 18.5% the existence of alternative solutions in absence of soap and water, 23.2% how to correctly wash hands. A lower incidence of SARS-CoV-2 infections was recorded in primary schools participating in the project as compared to the average regional incidence in Lombardy (9.6% vs.14.8%) and Apulia (10.7% vs.12.0%) for the same age group. Conclusions: We report an overall positive effect of health education interventions in primary schools. Although the limitations in the study design, our findings are important to inform planning, implementation and monitoring of health promotion campaigns in young generations so as to contribute to limit the risk of infection spread at the community level